Pembuatan Busana Pesta Malam dengan Mapping Tile Bordir pada Bagian Ekor Rok - Ningrum, Febrianita Yulia; Arifiana, Deny (Style : Journal of Fashion Design, 2023)
The aim of this study was to find out the process of making evening party dresses with embroidered tile mapping on the tail of the skirt and find out the results of making evening party clothes with embroidered tile mapping on the tail of the skirt. The method used in this study is the creation of work which consists of four stages. First, the pre-design stage. Second, the design stage. Third, the embodiment stage. Fourth, the presentation stage. The results of this study are: The process of making evening party dresses with mapping on the tail of the skirt starts from making a party dress design concept and making sketches. The process of applying mapping to party attire starts with cutting the embroidered tiles used for mapping according to the design. Then the embroidered tile pieces are arranged and placed on the tail of the party dress skirt. The finished result of making an evening party dress with embroidered tile mapping on the tail of the skirt is in accordance with the design concept. The selection of material characteristics using maroon duchess cloth and the application of embroidered tile mapping on the tail of the party dress skirt makes the dress look luxurious.